1969
DOI: 10.1002/sapm1969484377
|View full text |Cite
|
Sign up to set email alerts
|

Wave Instabilities

Abstract: A uniform train of periodic waves may be unstable to large scale variations so that some incoherence can develop. The analysis is presented for the case of gravity waves, and for a class of interaction problems typical of many physical systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
280
0
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(290 citation statements)
references
References 5 publications
9
280
0
1
Order By: Relevance
“…Among many other physical situations, the NLS equation arises as an approximate model of the evolution of a nearly monochromatic wave of small amplitude in pulse propagation along optical fibers (αβ > 0) [16], in gravity waves on deep water (αβ < 0) [3,11], and in Langmuir waves in a plasma (αβ > 0) [19]. As a description of a Bose-Einstein condensate, the NLS is known as the GrossPitaevskii equation (αβ > 0) [20,14].…”
Section: Introductionmentioning
confidence: 99%
“…Among many other physical situations, the NLS equation arises as an approximate model of the evolution of a nearly monochromatic wave of small amplitude in pulse propagation along optical fibers (αβ > 0) [16], in gravity waves on deep water (αβ < 0) [3,11], and in Langmuir waves in a plasma (αβ > 0) [19]. As a description of a Bose-Einstein condensate, the NLS is known as the GrossPitaevskii equation (αβ > 0) [20,14].…”
Section: Introductionmentioning
confidence: 99%
“…Yuen and Lake (1975), in turn, derived the NLS equation on the basis of the averaged Lagrangian method. Benney and Roskes (1969) extended those two-dimensional theories to the case of three-dimensional wave perturbations in a finite-depth fluid and obtained equations that are now known as the Davey-Stewartson equations. In this particular case, the equation proves the existence of the transverse instability of a plane wave, which is much stronger than a longitudinal one.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that gravity waves in infinite depth are long-wave unstable and suffer a side-band instability first identified both theoretically and experimentally by Benjamin & Feir (1967); the extension to finite depth fluid was provided by Benney & Roskes (1969). Superharmonic perturbations were investigated by Longuet-Higgins (1978), who found that the waves are stable if their amplitude does not exceed a critical value.…”
Section: Introductionmentioning
confidence: 99%